In vitro activity of Tedizolid and Dalbavancin against MRSA strains is dependent on infection source - Maya Azrad (International Journal of Infectious Diseases, 2019)
Objective: We tested the in vitro susceptibility to Tedizolid and Dalbavancin of Methicillin-resistant Staphylococcus aureus strains recovered from blood and wound cultures, and compared our results with studies conducted in the last four years. We examined whether the spa types affect the susceptibility of the different strains. Methods: We analyzed 275 Methicillin-resistant S. aureus strains recovered from 128 blood and 147 wound samples. For each strain, we performed minimum inhibitory concentration for Tedizolid and Dalbavancin and spa typing. We also performed a non-systematic review of the worldwide literature from the last four years concerning the in vitro activity of Tedizolid and Dalbavancin using the PubMed database; results were restricted by date of publication, between January 2015 and January 2018. Results: We found one Dalbavancin-resistant isolate (0.36%) and no resistance to Tedizolid. The minimum inhibitory concentration values were dependent in the strain source (wound vs. blood) for both antibiotics. For Dalbavancin, there was also dependence on the spa type. Conclusion: This study indicates Tedizolid and Dalbavancin have potent in vitro activity against the prevalent S. aureus clones in Israel. Further studies should be performed in order to uncover the factors contributing to reduced susceptibility of S. aureus strains to new drugs. Keywords: MRSA, Staphylococcus aureus, Tedizolid, Dalbavancin